Генетическая коллекция мейотических мутантов томата - Лісовська, Тетяна Павлівна; Коцун, Лариса Олександрівна; Кузьмишина, Ірина Іванівна; Lisovska, Tetiana P.; Kotsun, Larysa O.; Kuzmyshyna, Iryna I. (Інститут рослинництва ім. В.Я. Юр’єва, 2014)
Collection of meiotic mutants of tomato contains nine lines. Study collection of meiotic mutants of tomato using cytological, genetic, molecular genetic techniques is promising for the understanding of the basic steps of control processes that occur during meiotic division in higher plants.
Genetic collection of meiotic mutants of tomato